Light-ion production from a thin silicon target bombarded by 175 MeV quasi mono-energetic neutrons - S. Hirayama (2018)
Double-differential production yields of light ions (p, d, t,3He, and α) from a thin silicon target induced by 175 mev quasi mono-energetic neutrons were measured using the MEDLEY setup at the The Svedberg Laboratory (TSL) in Uppsala in order to benchmark evaluated nuclear data and nuclear reaction models. The MEDLEY is a conventional spectrometer system which consists of eight counter telescopes. Each telescope is composed of two silicon surface barrier detectors as the ΔE detectors and a CsI(Tl) scintillator as the E detector for particle identification. The telescopes are placed at angles from 20° to 160° in steps of 20°. The measured double-differential yields of light ions are compared with PHITS calculations using the following nuclear reaction options: the high-energy nuclear data library (JENDL/HE-2007), the quantum molecular dynamics (QMD) model, and the intra-nuclear cascade (INC) model.